Perancangan Website Dengan Metode Waterfall Di Kabupaten Ciamis (Study Kasus Di Komunitas Peduli Alam Dan Lingkungan Galuh Ciamis) - Usep Abdul Rosid; Sidiq, Maulana; Mulyana, Dadan; Yudi Permana, Nana (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2023)
Pedal Gas is an abbreviation of the name of the community organization or NGO Paguyuban Peduli Alam dan Lingkungan Galuh Asri. Declared in Ciamis Regency, West Java by a group of activists who care about the preservation of nature and the environment. Information on community activities still uses a manual system, namely by attaching activity brochures to the announcements that have been provided, therefore to be able to provide information while promoting activities organized by nature care community organizations, facilities are needed in the form of a website that will be designed using the waterfall method with the results in the form of a website prototype design. With the design of the website, it can help the community in developing a web-based system which in the future is expected to be more familiar with Pedal Gas and the community and can add promotional facilities for every activity through the website.